Respuesta :

Answer:

Step-by-step explanation:

It's given in the question,

[tex]2^x=3^y=12^z[/tex]

[tex]2^x=12^z[/tex]

[tex]\text{log}2^x}=\text{log}12^z}[/tex]

[tex]x\text{log2}=z\text{log12}[/tex]

[tex]x=\frac{z\text{log}12}{\text{log2}}[/tex]

[tex]3^y=12^z[/tex]

[tex]\text{log}3^y}=\text{log}12^z}[/tex]

[tex]y\text{log}3}=z\text{log}12}[/tex]

[tex]y=\frac{z\text{log12}}{\text{log}3}[/tex]

Now substitute the values in the equation,

[tex]\frac{1}{y}+\frac{2}{y} =\frac{1}{\frac{z\text{log12}}{\text{log}3}}+\frac{2}{\frac{z\text{log}12}{\text{log2}}}[/tex]

         [tex]=\frac{\text{log}3}{z\text{log}12}+\frac{2\text{log}2}{z\text{log}12}[/tex]                    

         [tex]=\frac{\text{log}3+\text{log}2^2}{z\text{log}12}[/tex]

         [tex]=\frac{\text{log}(3\times 2^2)}{z\text{log}12}[/tex]

         [tex]=\frac{\text{log}(12)}{z\text{log}12}[/tex]

         [tex]=\frac{1}{z}[/tex]

Hence proved.

ACCESS MORE